A Facile Synthetic Approach to Nonracemic Substituted Pyrrolo-allocolchicinoids Starting from Natural Colchicine - Shchegravina, Ekaterina S.; Svirshchevskaya, Elena V.; Schmalz, Hans-Günther; Fedorov, Alexey Yu (Synthesis, 2019)
A six-step semisynthetic approach towards chiral nonracemic pyrrolo-allocolchicinoids starting from naturally occurring colchicine was developed. The synthetic scheme includes an electrocyclic tropolone ring contraction to afford allocolchicinic acid followed by the Curtius reaction, giving the corresponding aniline. The Sandmeyer reaction and copper-mediated hydrazination gave hydrazine-substituted allocolchicine. This was introduced into the Fischer indole synthesis, affording libraries of regioisomeric indole-based allocolchicine congeners.
Keywords: colchicine; pyrrolo-allocolchicinoids; Fischer indole synthesis; tubulin; anti-tubulin agents